2019
DOI: 10.1016/j.sjbs.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Studies on wound healing potential of red pigment isolated from marine Bacterium Vibrio sp.

Abstract: Wounds are common clinical entities of life which may be subacute or acute. Wound healing is a complex biochemical process where the cell structures are restored to normalcy, which depend on cell proliferation and migration, basically fibroblast cell. The present investigation was undertaken to evaluate the healing efficacy of red pigment isolated from marine isolate Vibrio sps on experimental wounds in albino rats. The red pigment was applied topically, twice daily for 14 days. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…Initially plant derivatives were used to use numerous drugs used in conventional medicine ( Oreagba et al, 2011 ). In the recent study, Shiva et al (2019) confirmed faster reduction in wound area from red pigment in comparison with control and framycetin ointment treated groups and indicated that red pigment shown significant wound healing potential with positive influence on wound repair phases.
Fig.
…”
Section: Resultsmentioning
confidence: 65%
“…Initially plant derivatives were used to use numerous drugs used in conventional medicine ( Oreagba et al, 2011 ). In the recent study, Shiva et al (2019) confirmed faster reduction in wound area from red pigment in comparison with control and framycetin ointment treated groups and indicated that red pigment shown significant wound healing potential with positive influence on wound repair phases.
Fig.
…”
Section: Resultsmentioning
confidence: 65%
“…The dynamic pathogenetic process of the healing of acute wounds depends on the balance of such factors as oxygenation, temperature, and pH [12,[24][25][26]. It consists of several successive and interrelated phases: coagulation (hemostasis), inflammation, fibroblast proliferation, and tissue remodeling [23,[27][28][29][30] (Figure 1). The initial stage is aimed at preventing excessive blood loss, for which it triggers the hemostatic mechanisms in response to bleeding [19,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the inflammatory phase is accompanied by activation of fibronectin synthesis induced by growth factors, as well as by migration of fibroblasts-pluripotent stromal cells that dominate cell populations on the first day and play a significant role in healing-towards the wound [11,30,33]. During this period, a large number of mediators are released into the wound, thus, providing the process of granulation formation, including proangiogenic growth factors that initiate the proliferation and organization of vascular endothelial cells [27,29,34,35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations